Temperature-dependent vortex matter in a superconducting mesoscopic circular sector - Barba-Ortega, J.; Sardella, Edson [UNESP]; Aguiar, J. Albino (Elsevier B.V., 2010)
Nonlinear time-dependent Ginzburg-Landau (TDGL) equations were solved in the present work using the link variables method. Vortex configurations were investigated in a superconducting circular sector immersed in an external magnetic field applied perpendicular to its plane. Magnetization and free energy were calculated as a function of the applied magnetic field at several temperatures. This paper illustrates how the vortices moved around at the transition fields before they become accommodated into an equilibrium configuration. A linear dependence of the magnetization dependence on temperature has been found for a certain magnetic field. Crown Copyright (C) 2010 Published by Elsevier B.V. All rights reserved.
Keywords: Link variable method; Ginzburg-Landau; Mesoscopic circular sector